Bioremediation of industrial effluents: How a biochar pretreatment may increase the microalgal growth in tannery wastewater. (October 2020) - Sforza, Eleonora; Kumkum, Pushpita; Barbera, Elena; Kumar, Sandeep
Graphical abstract: Highlights: Biochar pretreatment improved significantly C. protothecoides growth in tannery wastewater. Biochar physio-chemical characteristics strongly affect chromium adsorption capacity. Cr(III) adsorption on commercial biochar followed Freundlich isotherm model and pseudo-second order kinetics. The variability and complexity of tannery wastewaters affect the performances of the combined process. Abstract: The application of microalgae in wastewater treatment is gaining increasing attention due to the possible environmental benefits of using photosynthetic organisms for bioremediation. Tannery wastewaters, however, may be inhibiting for microorganisms' growth due to the presence of toxic compounds, especially chromium. In this work, we assessed the possibility of combining the application of biochar, as an adsorbent for metals including chromium, with microalgae cultivation for tannery wastewater treatment. Two different types of biochar (pinewood biochar, PB, and a commercial one, CB) were tested as a pretreatment step prior to cultivation of Chlorella protothecoides . The application of both types of biochar led to a significant increase in growth rates (61 % and 126 % for PB and CB, respectively) and nutrients removal compared to cultivation in raw wastewaters. Concerning the comparison between different biochars, it resulted that biochar production process and its physiochemical characteristics strongly affect Cr(III) adsorption performances, with CB removing 99.6 % from a synthetic medium in 5 min, compared to 83.4 % of PB in 3 h. Cr(III) adsorption on CB followed Freundlich isotherm model. The kinetics of adsorption was also addressed, and pseudo-second order kinetics was found to be the best fitted model for Cr(III) adsorption on CB. When applied to real tannery effluents, chromium adsorption performances were affected by the complexity of the medium